(Re)Kindle: On the Value of Storytelling to Technical Communication. (April 2017) - Small, Nancy
In an effort to expand the range of ways graduate programs prepare students to be scholars and practitioners in technical and professional communication, this article argues for a fresh direct reengagement with stories, storytelling, and narrative as valuable ways of studying and effectively producing the varied texts of the workplace. The previous call for acknowledging the value of narrative traces back almost 30 years, and story is still being used in a variety of compelling ways, even as an overt regard for narrative has not been sustained. What may be lacking is a systematic way to transform assumptions about stories as informal anecdotes into stories as data for rigorous analysis. David Boje's antenarrative theory and method offers technical and professional communication graduate students, scholars, and practitioners just such a compelling and timely position from which to consider workplace processes and products.